THE DEVELOPMENT OF LONG JUMP STYLE SQUAT LEARNING MODEL BASED ON SAINTIFIC APPROACH - Efran Saputra; Syafruddin Syafruddin; Hartati Hartati (Sriwijaya University Learning and Education International Conference, 2018)
The development of learning model of long jump squat style based on scientific approach in junior high school students was conducted to obtain information about students' abilities including affective, cognitive and psychomotor spheres in learning long jump. The design in this research using research and development model approach (Research & Development). While the subjects in this study are all first grade students in Srijaya Negara and Mandiri Junior High School Palembang amounted to 32 people. The instruments used in this study were questionnaires, questionnaires, assessment rubbers, methods of need analysis, initial product design, expert validation, design improvements, small group trials, product revisions, large group trials, product revisions and final products. Result of validation model with value 78,4% good criterion, rublik aspect appraisal 81,33% good criterion, for significant level using spss where got t count 7,33323> t table 2,039 Ho rejected no significant difference. In conclusion, the development of learning model long jump style squat based on scientific approach in junior high school students produce an effective product to improve psychomotor aspects, cognitive aspects and affective aspects. It is recommended for physical education teachers to be able to use this learning model as supporting learning material of long jump in school.